ASSESSMENT OF THE EFFICIENCY OF FIRE EXTINGUISHING SYSTEMS - Abramov, Yu.; Kolomiiets, V.; Sobyna, V. (Municipal economy of cities. Series: «Economy science», 2024)
As previously shown, many indicators characterise the quality of fire extinguishing systems. The most common quality indicator is fire extinguishing time. For fire extinguishing systems focused on extinguishing Class B fires using sprayed water, the authors have constructed a transcendental equation, the root of which is the fire extinguishing time. We derived the equation provided that the intensity of the sprayed water supply to the combustion centre to be described by the Heaviside function. The dynamic properties of fire are defined using the integral Laplace transform. We obtained the functional dependence of class B fire extinguishing time on fire parameters and showed that this time does not exceed a tenth of the constant fire time. In the first approximation, the inertial properties of the fire extinguishing system can be taken into account by the transfer function of an aperiodic link with a generalised time constant. For this case, we constructed a transcendental equation that determines the fire extinguishing time by the inertial fire extinguishing system. We note that, according to inertial properties, fire extinguishing systems fall into three classes. For each of the three classes, estimates of the extinguishing time of a class B fire were obtained, depending on the dynamic properties of this fire. The results show that this time can change several times. The authors have introduced the criterion for the efficiency of fire extinguishing systems, which characterises the degree of approximation of the speed of the fire extinguishing system to the maximum possible value. This criterion also indicates how much it is necessary to increase the extinguishing agent mass supplied per unit area of the fire relative to the extinguishing agent mass supplied in leaps per unit area of the fire, provided that the extinguishing times are the same. We obtained estimates of the effectiveness of fire extinguishing systems using this criterion. Furthermore, we provided recommendations on the use of the efficiency criterion.